Pengaruh Pendidikan Kesehatan Audiovisual Terhadap Pengetahuan dan Sikap Remaja tentang Kehamilan Dini di MTsN Penajam: English - Wijayanti, Endah; Supriyadi, Supriyadi; Azizah, Siti (Malang Journal of Midwifery (MAJORY), 2023)
Adolescents are a group that is vulnerable to early pregnancy and the pregnancy rate in adolescents is still high. Teenage pregnancy has a negative impact on the health of adolescents and their babies, it can also have social and economic impacts. Pregnancy at a young age or adolescence includes the risk of premature birth, low birth weight (LBW), childbirth bleeding, which can increase maternal and infant mortality. The research method is a quasi-experimental design with a one group pretest – posttest design, the population was all female students at MTs Negeri 3 with a sample of 40 students. The sampling technique is stratified random sampling. The research instrument is a questionnaire. The data analysis technique used central tendency and dependent t test. The result was knowledge of prehealth education average value (mean) 10.33 after being given health education an average value of 17.70, the attitude of students before being given health education an average value of 40.18 and after being given health education an average value of 63,08. There is an effect of health education using audiovisual on knowledge and attitude was p value 0.000. Health education using audiovisual results in increasing adolescent knowledge and attitudes towards early pregnancy because audiovisuals make it easier to convey information and are easy to remember because the media involves hearing, seeing and being interesting